Antimicrobial Resistance Rates and Treatment Options in Bloodstream Infections: A Prospective Observational Study - Lal Sude Gücer; Fatihan Pınarlık; Refath Farzana; Nazlı Ataç; ZELİHA GENÇ; Bahar Madran; IREM SENA BULBUL; Feyza Şahin; Buket ERTURK SENGEL; Elif Tukenmez Tigen; Arzu Ilki; NURAN SARI; et al. (Journal of Global Antimicrobial Resistance, 2024)
Background: Emerging antibacterial resistance is a constant threat. Broad-spectrum antibiotics are preferred in empirical treatment for bloodstream infections (BSI) due to increasing resistance rates. METHODS: A prospective observational study was conducted in three tertiary hospitals in Türkiye. Microbiologically documented BSIs were collected between 1 November 2023 and 1 June 2024. Demographics, clinical information, and antimicrobial susceptibility tests for each BSI case were collected. RESULTS: A total of 618 BSI patients were included in the study and 55 (8.9%) of these BSIs were polymicrobial. Among 563 monomicrobial BSIs, the causative agent was gram-negative in 278 (49.4%), gram-positive in 247 (43.9%), and Candida spp. in 38 (6.7%) patients. Gram-positive and gram-negative species distribution is depicted in Figure 1 and 2, respectively. Methicillin-resistant S. aureus (MRSA) rate was 37%. Carbapenem resistance rate for K. pneumoniae was 62%. 30-day mortality was 48% in gram-negative BSI, and it was 66% if the causative agent is carbapenem resistant. BSI caused by MRSA had a 30-day mortality of 36%. The two most common empirical treatment choices were meropenem and piperacillin-tazobactam. Of patients receiving ineffective empirical treatment, 35% failed escalation in 24 hours after susceptibility results. More than 24-hour delay in de-escalation of meropenem was observed in 82% of gram-negative BSIs. Escalation in 24 hours was achieved in MRSA BSIs. Mean delay of 3.9 days were observed in de-escalation of vancomycin or teicoplanin in methicillin-susceptible S. aureus BSIs. CONCLUSION: Timely transition to targeted therapies is critical for antimicrobial stewardship especially when broad-spectrum antibiotics are preferred in empirical therapy.